1991
DOI: 10.1210/endo-129-2-1049
|View full text |Cite
|
Sign up to set email alerts
|

In VivoRegulation of the Activity of the Two Promoters of the Rat Acetyl Coenzyme-A Carboxylase Gene*

Abstract: The acetyl-coenzyme-A carboxylase (ACC) gene contains two promoters: promoter I (PI) and promoter II (PII). Depending upon which promoter is active, two classes of ACC mRNA are formed. The physiological significance of the presence of two promoters in the gene is not clear at this time. However, this question can be indirectly approached by examination of their expression patterns under different physiological conditions. We have examined the activities of these two promoters under different physiological cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 0 publications
5
55
1
Order By: Relevance
“…Acetyl-CoA mRNA is induced in mammalian liver after a high carbohydrate diet (32,33). Because we had found that (48) that was used as a positive control for the His-tag antibody in this experiment.…”
Section: Dominant Negative MLX Efficiently Blocks Induction Of Endogementioning
confidence: 99%
“…Acetyl-CoA mRNA is induced in mammalian liver after a high carbohydrate diet (32,33). Because we had found that (48) that was used as a positive control for the His-tag antibody in this experiment.…”
Section: Dominant Negative MLX Efficiently Blocks Induction Of Endogementioning
confidence: 99%
“…On the other hand, the proximal promoter lacks a TATA or CAAT box, thus exhibiting features of a housekeeping promoter. Transcripts produced from this type of promoter are expressed constitutively (43). In addition, when transcripts are generated from two promoters, they have been shown to have different translation efficiencies (44).…”
Section: Organization Of the Coding Exons-mentioning
confidence: 99%
“…However, administration of insulin to streptozotocindiabetic rats further activates both promoters, regardless of the type of diet given to the starved animals [27]. In contrast, only PI -and not PII -responds to nutritional induction in white adipose tissue [28]. It has been shown recently that the CCAAT\ enhancer-binding protein (C\EBP) may be one of the factors that is responsible for the activation of promoter PI under lipogenic conditions [29].…”
Section: Introductionmentioning
confidence: 99%